Finite-element modelling of 3D timber structures Efficient pre- and postprocessing modelling strategies for 3D timber shear walls - Götberg, Filip (My University, 2022)
This thesis investigates, develops and proposes finite-element modelling strategies for timber shear walls constructed as timber frame walls and cross-laminated timber walls. The thesis recommends various techniques to reach reliable results and at the same time reduce the modelling efforts. Studies are made on the effects of scaling the structure to multiple floors as well as the influence of the length of the individual wall elements. Discussions are made on the behaviour of the different modes of deformation and it is found that there is a significant potential to reduce the calculated deformation of timber shear walls by taking into account the friction to the foundation or floor as well as considering the weak axis strength of shear and tension connectors. Further a discussion is held concerning modelling strategies suitable for linear dynamic analysis and recommendations are made to take precautions of how the non-linearities in the model are linearized in the analysis.
Keywords: Timber structure, Shear wall, Finite-element method, Modelling strategy, Stiffness assessment.